Equivalence of the insulin sensitivity index in man derived by the minimal model method and the euglycemic glucose clamp - Richard N. Bergman; Rudy Prager; Aage Volund; Jerrold M. Olefsky (The Journal of Clinical Investigation, 1987)
Studies were done to determine whether the minimal model approach and the glucose clamp measure equivalent indices of insulin action. Euglycemic glucose clamps (glucose, G: 85 mg/dl) were performed at two rates of insulin (I) infusion (15 and 40 mU/min per m2) in 10 subjects (body mass index, BMI, from 21 to 41 kg/m2). Insulin sensitivity index (SI) from clamps varied from 0.15 to 3.15 (mean: 1.87 +/- 0.36 X 10(-2) dl/[min per m2] per microU/ml), and declined linearly with increasing adiposity (versus BMI: r = -0.97; P less than 0.001). SI from modeling the modified frequently sampled intravenous tolerance test varied from 0.66 to 7.34 X 10(-4) min-1 per microU/ml, and was strongly correlated with SIP(clamp) (r = 0.89; P less than 0.001). SI and SIP(clamp) were similar (0.046 +/- 0.008 vs. 0.037 +/- 0.007 dl/min per microU/ml, P greater than 0.35); the relation had a slope not different from unity (1.05 P greater than 0.70) and passed through the origin (P greater than 0.40). However, on a period basis, SI exceeded SIP(clamp) slightly, due to inhibition of hepatic glucose output during the FSIGT, not included in SIP(clamp). These methods are equivalent for assessment of overall insulin sensitivity in normal and insulin-resistant nondiabetic subjects.